Click chemistry: 1,2,3-triazoles as pharmacophores - Agalave, Sandip G.; Maujan, Suleman R.; Pore, Vandana S. (Chemistry-an Asian Journal, 2011)
The copper(I)-catalyzed 1,2,3-triazole-forming reaction between azides and terminal alkynes has become the gold standard of `click chemistry' due to its reliability, specificity, and biocompatibility. Applications of click chemistry are increasingly found in all aspects of drug discovery; they range from lead finding through combinatorial chemistry and target-templated in vitro chemistry, to proteomics and DNA research by using bioconjugation reactions. The triazole products are more than just passive linkers; they readily associate with biological targets, through hydrogen-bonding and dipole interactions. The present review will focus mainly on the recent literature for applications of this reaction in the field of medicinal chemistry, in particular on use of the 1,2,3-triazole moiety as pharmacophore.
Keywords: Click chemistry; Copper; Cycloaddition; pharmacophores; triazoles